Operative Time, Age, and Serum Albumin Predict Surgical Morbidity After Laparoscopic Liver Surgery. (December 2021) - Heise, Daniel; Bednarsch, Jan; Kroh, Andreas; Schipper, Sandra; Eickhoff, Roman; Lang, Sven; Neumann, Ulf; Ulmer, Florian
Background . Laparoscopic liver resection (LLR) has emerged as a considerable alternative to conventional liver surgery. However, the increasing complexity of liver resection raises the incidence of postoperative complications. The aim of this study was to identify risk factors for postoperative morbidity in a monocentric cohort of patients undergoing LLR. Methods . All consecutive patients who underwent LLR between 2015 and 2019 at our institution were analyzed for associations between complications with demographics and clinical and operative characteristics by multivariable logistic regression analyses. Results . Our cohort comprised 156 patients who underwent LLR with a mean age of 60.0 ± 14.4 years. General complications and major perioperative morbidity were observed in 19.9% and 9.6% of the patients, respectively. Multivariable analysis identified age>65 years (HR = 2.56; P = .028) and operation time>180 minutes (HR = 4.44; P = .001) as significant predictors of general complications (Clavien ≥1), while albumin<4.3 g/dl (HR = 3.66; P = .033) and also operative time (HR = 23.72; P = .003) were identified as predictors of major postoperative morbidity (Clavien ≥3). Conclusion . Surgical morbidity is based on patient- (age and preoperative albumin) and procedure-related (operative time) characteristics. Careful patient selection is key to improve postoperative outcomes after LLR.